Vitamin E ameliorates neurodegeneration related phenotypes caused by neurotoxicity of Al2O3-nanoparticles in C. elegans. Issue 5 (22nd June 2015) - Yu, Xiaoming; Guan, Xiangmin; Wu, Qiuli; Zhao, Yunli; Wang, Dayong
Graphical Abstract: Abstract: We investigated the protective effects of vitamin E against the in vivo neurotoxicity of Al2 O3 -nanoparticles (NPs) in Caenorhabditis elegans . Al2 O3 -NPs in the range of mg L −1 led to neurodegeneration related phenotypes including neuronal loss, abnormality of axon development, and gap formation on nerve cords in the GABAergic nervous system and some behavioral deficits. Pretreatment with 200 mg L −1 of vitamin E prevented the neurotoxicity of Al2 O3 -NPs by reducing both the neurodegeneration and behavioral deficits. As for the underlying mechanism, pretreatment with vitamin E prevented the induction of oxidative stress, and sustained the normal intestinal permeability and development in Al2 O3 -NPs exposed animals. Moreover, pretreatment with vitamin E inhibited the translocation of Al2 O3 -NPs through the intestinal barrier into other parts of nematodes. Vitamin E-pretreated animals also showed less abnormality in the development of neurons involved in behavioral control and expression pattern of genes regulating cell identity of the corresponding neurons. Our results will be helpful for designing effective strategies to ameliorate nanotoxicity.